Algorithm for modeling possible failures at the construction site - Pichugin, Sergiy (Academic journal Industrial Machine Building Civil Engineering, 2022)
This article presents the main prerequisites for the development of an algorithm for modeling the possible accident occurrence at the construction site. The paper presents statistical information of the buildings and structures accidents for 2000-2022. The article proposes an algorithm for modeling the possible accident occurrence for use in design documentation in construction. The modelling algorithm is presented in the form of a block diagram, the main provisions for its implementation are described. The developed algorithm is based on the results of statistical processing of information on buildings and structures accidents and can be performed by design engineers on the basis of visual three-dimensional model of the designed building
Keywords: statistics; modeling; accident; building; probability of an accident; destruction; consequences; systematization